IMPLEMENTATION OF MIND MAPPING LEARNING MODEL TO IMPROVE STUDENTS' CREATIVITY IN SCIENCE LESSONS IN GRADE III OF SD GMIT KUANINO 1 KUPANG CITY - Dira Ndoluanak; Femberianus S. Tanggur; Asti Y. Benu; Yulsi M. Nitte (Universitas Citra Bangsa, 2025)
The mind mapping learning model is a visualization technique that helps students organize information, plan ideas, and connect concepts more effectively. By using mind mapping, students can be more active in the learning process, so that they can improve their absorption and understanding of the material being taught. By actively involving students in learning, it is hoped that they can develop creative and innovative thinking skills, and gain a deeper understanding of science and natural sciences material. This study aims to examine the implementation of the mind mapping learning model in improving student creativity in science and natural sciences learning in grade 3 of GMIT Kuanino 1 Elementary School, Kupang City. The method used in this study is a type of qualitative research with a descriptive method. The data collection instruments in this study were observation sheets, interview guidelines, documentation studies. And the data analysis techniques used in this study were Data Collection, Data Reduction, Data Verification, and Data Presentation. The results of the study showed thatThe implementation of this method significantly increases students' creativity and engagement in the learning process. Students show high enthusiasm and active involvement during the mind mapping process, which not only makes them understand the subject matter better, but also encourages them to dare to express ideas through image visualization and the use of color.